Analisis Kualitas Pelayanan Diversi Dalam Memberikan Perlindungan Hukum Anak Di Balai Pemasyarakatan Kelas I Manado - Simboh, Octavianus D.W; Mamonto, Fitri H; Wawointana, Thelma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to understand and evaluate the standard of diversion services, along with factors that support or hinder the quality of diversion services in providing legal protection for children at the Manado Class I Correctional Center. The type of research used in this research is descriptive qualitative and the collection techniques are observation, interview and documentation. In general, the results of the research and discussion above can be concluded 1) The quality of diversion services in providing legal protection for children at the Manado Class I Correctional Center has not been effective, 2) There are 6 (six) supporting factors: (a) The availability of legality, legal umbrella, (b) The availability of opportunities for recruitment of new CPNS personnel, (c) Training institutions are available, (d) The availability of a budget that can be submitted (e) There is a control institution (f) There is support from all parties both from the police, prosecutor's office, court, family of the perpetrator or victim to take the diversion route, deliberation consensus rather than continuing the case to the green table.